Using the given information, the equation of the circle with radius 7 and center located at (-6 , 13) is (x + 6)^2 + (y - 13)^2 = 49.
The general form of the equation of circle is given by (x - h)^2 + (y - k)^2 = r^2, where (h , k) is the location of the center and r is the radius of the circle.
Given the radius and center of the circle, substitute these values to the general form of the equation of the circle.
(x - h)^2 + (y - k)^2 = r^2
where (h , k) = (-6 , 13)
r = 7
(x - -6)^2 + (y - 13)^2 = 7^2
(x + 6)^2 + (y - 13)^2 = 49
Learn more about equation of a circle here: https://brainly.com/question/14150470
#SPJ4